Tajemnica przysposobienia w ujęciu prawa o aktach stanu cywilnego z 29 września 1986 roku - Ignatowicz, Jerzy (Wydział Prawa i Administracji UAM, 1987)
The article presents the process of shaping the principle of secrecy of. adoption in the Polish law together with a detailed analysis of regulations pertaining to the above issue contained in the Law on Civil Status Acts of 1986. Since the Law creates a highly complicated system of concealing the origin of an adopted child its application may cause difficulties in practice. Intricate problems arise with respect to the interpretation of regulations providing for drawing out a new birth certificate with adopters registered as the parents of the adopted child. In the author's opinion, such a certificate should be drawn out in the cases of 1) irrevocable adoption by the spouses jointly or by a single person, 2) full adoption of a step-child by a step-parent (a controversial issue), 3) full adoption by the spouses jointly, if the court, at the instance of the adopters, decided so; the latter possibility is an important novelty introduced by the Law of 1986. In the author's opinion, the line of the legislative changes concerning the secrecy of adoption fully responds to the expectations of the society. However, the new regulation requires somewhat more precision and needs to be better coordinated with Family and Guardianship Code provisions. Besides, it raises doubts also because it does not eliminate the possiblity of obtaining the information as to the origin of a child by informal channels. Such information should, however, be disclosed if the court requires so, whenever there is the danger of concluding marriage despite the obstacle of consanguinity.
The secrecy of adoption in view of the Law on Civil Status Acts of Sept. 29, 1986